Lanskap Suci dan Perlindungan Lingkungan di Gunung Pegat, Srengat, Blitar: Mitologi Punokawan Sebagai Mekanisme Konservasi Informal - Farika Azza Kamila; Dian Yasmina Fajri; A. Zahid (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Mount Pegat in Blitar Regency is an area with strong cultural and spiritual values ​​through the Punokawan mythology passed down through generations by the local community. Beliefs in sites such as Sawah Semar and Sumur Kahuripan not only shape the sacredness of the area but also influence how the community interacts with the environment. This study aims to analyze the construction of the sacred landscape of Mount Pegat, the role of Punokawan mythology as an informal conservation mechanism, and the process of sacred reproduction in the community's social life. The study used a qualitative approach with ethnographic methods. Data were obtained through observation, in-depth interviews, and documentation involving community leaders, area managers, and local residents. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using Anthony Giddens' structuration theory as an analytical tool. The results show that Punokawan mythology plays a role in the cultural structure that shapes the community's understanding of Mount Pegat as a sacred landscape. The beliefs and norms that develop in the community encourage behavior to protect vegetation, water sources, and sacred sites, resulting in informal conservation practices. The sacredness of the area continues to be maintained through the transmission of oral stories, the role of community leaders, and daily social practices that reproduce these cultural values. Research findings indicate that environmental conservation can thrive through local belief systems that are alive within the community, thus fostering a mutually reinforcing relationship between culture and the environment in maintaining the sustainability of the sacred landscape.